Dynamics of Fictional Positionings in Paul Auster's Travels in the Scriptorium. Issue 3 (27th May 2017) - Barani, Forough; Wan Yahya, Wan Roselezam
ABSTRACT: Paul Auster blends stories with stories, lives with lives, and reality with fiction, and, finally, presents a full sense of the self trapped in a net of uncertainties. In this article, we examine the fictional positioning of Auster's protagonist in Travels in the Scriptorium (2006/2007) to identify the role of storytelling in authoring one's self. Based on the newly developed conceptual framework of "virtual fictional and factual positioning, " we elaborate on the possible dialogical coalition of the author's positions as "I-as-artist/novelist" and "I-as-the-hero-of-my-story, " among other positions. The findings of this research indicated that the art of storytelling for Mr Blank becomes a means of survival. In his creative absorption in the fictional and factual positionings and experiencing the life of his hero, Mr Blank as a motivated artist/novelist could develop a dialogical self and reconstitute a more porous sense of his self and identity.